2011
DOI: 10.1037/a0022331
|View full text |Cite
|
Sign up to set email alerts
|

Functional equivalence of spatial images from touch and vision: Evidence from spatial updating in blind and sighted individuals.

Abstract: This research examines whether visual and haptic map learning yield functionally equivalent spatial images in working memory, as evidenced by similar encoding bias and updating performance. In three experiments, participants learned four-point routes either by seeing or feeling the maps. At test, blindfolded participants made spatial judgments about the maps from imagined perspectives that were either aligned or misaligned with the maps as represented in working memory. Results from Experiments 1 and 2 reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
80
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 69 publications
15
80
3
Order By: Relevance
“…The claim that people construct similar representations after encoding information from different modalities (i.e., vision, touch, language) is supported by various studies which provided evidence that different modalities lead to functionally equivalent spatial representations (e.g., Avraamides & Kelly, 2010;Giudice, Betty, & Loomis, 2011;Mello, Greenauer, Pantelidou, & Avraamides, under revision;Pantelides, 2010). Functional equivalence indicates that performance in a spatial task is independent of the input modality (e.g., Giudice, Betty, & Loomis, 2011;Avraamides & Pantelidou, 2008).…”
Section: Integration Of Spatial Information Across Vision and Languagementioning
confidence: 99%
See 1 more Smart Citation
“…The claim that people construct similar representations after encoding information from different modalities (i.e., vision, touch, language) is supported by various studies which provided evidence that different modalities lead to functionally equivalent spatial representations (e.g., Avraamides & Kelly, 2010;Giudice, Betty, & Loomis, 2011;Mello, Greenauer, Pantelidou, & Avraamides, under revision;Pantelides, 2010). Functional equivalence indicates that performance in a spatial task is independent of the input modality (e.g., Giudice, Betty, & Loomis, 2011;Avraamides & Pantelidou, 2008).…”
Section: Integration Of Spatial Information Across Vision and Languagementioning
confidence: 99%
“…Functional equivalence indicates that performance in a spatial task is independent of the input modality (e.g., Giudice, Betty, & Loomis, 2011;Avraamides & Pantelidou, 2008). Notably, findings by a number of studies revealed that people perform in an equivalent manner in spatial tasks (i.e., JRD's) after they learn locations from vision, touch, and also spatial language (e.g., Avraamides et al, 2004;Giudice et al, 2011). Particularly, two views account for the hypothesis that functional equivalence may result from the convergence of spatial information from different modalities to a single representation (e.g., Loomis, Lippa, Golledge, & Klatzky, 2002).…”
Section: Integration Of Spatial Information Across Vision and Languagementioning
confidence: 99%
“…Then, following the analysis method introduced by Wang and Spelke (2000) and adapted by Mou, McNamara, Rump, and Xiao (2006;see also Xiao, Mou, & McNamara, 2009;Xiao & Zhang, 2013), we computed each participant's heading error, pointing variability, and configuration error from each imagined perspective. This type of analysis of pointing errors had not been conducted in the previous studies of map learning discussed earlier (e.g., Giudice et al, 2011;Presson et al, 1989;Presson & Hazelrigg, 1984), and so is novel to this study.…”
Section: Analysis Of Sources Of Pointing Errorsmentioning
confidence: 96%
“…If the map was small, the participants made less-accurate directional judgments (i.e., with more angular error) when their facing direction was contraligned with the learning direction than when it was aligned, suggesting that they were unable to update their spatial representation. In contrast, in one condition of a related study, employing the same type of small four-point-route map (0.4 × 0.4 m), Giudice, Betty, and Loomis (2011) had people learn a map and then rotate in place while leaving the map behind them (rotate without map). After rotation, the researchers observed that participants performed equivalently from the learning direction and from their facing direction, suggesting that the participants were able to update their spatial representation.…”
Section: Alignment Effect Sensorimotor Alignment Effectmentioning
confidence: 99%
“…For example, they can turn to face and point to targets after walking toward or away from them (Horn & Loomis, 2004;Kennedy, 1993;Loomis & Philbeck, 2008). After learning four-point routes from tactile or visually inspected maps, blind and sighted adults were asked to imagine perspectives aligned or misaligned with maps they studied (Giudice, Betty, & Loomis, 2011). Blind and sighted participants had similar patterns of errors and latencies.…”
mentioning
confidence: 99%